2016
DOI: 10.1126/scitranslmed.aag2374
|View full text |Cite
|
Sign up to set email alerts
|

Oral, ultra–long-lasting drug delivery: Application toward malaria elimination goals

Abstract: Efforts at elimination of scourges, such as malaria, are limited by the logistic challenges of reaching large rural populations and ensuring patient adherence to adequate pharmacologic treatment. We have developed an oral, ultra–long-acting capsule that dissolves in the stomach and deploys a star-shaped dosage form that releases drug while assuming a geometry that prevents passage through the pylorus yet allows passage of food, enabling prolonged gastric residence. This gastric-resident, drug delivery dosage f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
217
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(220 citation statements)
references
References 43 publications
1
217
0
2
Order By: Relevance
“…[13,14] A recent study revealed the potential of Ac2-26 for the treatment of colitis after intraperitoneal or intramucosal injection of Ac2-26 in nanoparticles (NPs). [16][17][18][19][20][21] However, there are still tremendous challenges in the design and development of translational nanovehicles for oral delivery of macromolecular therapeutics, [16,[22][23][24][25] although different nanotherapies have been developed for targeted treatment of IBD. On the other hand, patient-friendly oral delivery is highly preferred for treatment of gastrointestinal and chronic diseases, owing to its convenience, high patient compliance, desirable cost-effectiveness, and good safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] A recent study revealed the potential of Ac2-26 for the treatment of colitis after intraperitoneal or intramucosal injection of Ac2-26 in nanoparticles (NPs). [16][17][18][19][20][21] However, there are still tremendous challenges in the design and development of translational nanovehicles for oral delivery of macromolecular therapeutics, [16,[22][23][24][25] although different nanotherapies have been developed for targeted treatment of IBD. On the other hand, patient-friendly oral delivery is highly preferred for treatment of gastrointestinal and chronic diseases, owing to its convenience, high patient compliance, desirable cost-effectiveness, and good safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…While there have to be enough clusters to meet tests for robustness given hypothesized effect size, and the specifics of the control intervention package may vary, there are, conceptually, some key elements to consider:

A vector control package representative of strategies and epidemiology for that region must be included.

Appropriate surveillance system for identification of cases and appropriate response systems must be in place. This includes reporting systems to ensure timely facility-based reporting.

The impact of ivermectin MDA is modelled to be proportionally higher in areas of high transmission [44, 56], giving a theoretical power advantage to that context, although trials under different scenarios (higher endemicity to accelerate the path to elimination and at low levels of endemicity to accelerate crashing transmission) have been considered and would be valuable in different context.
…”
Section: Introductionmentioning
confidence: 99%
“…Forexample,the abrupt and conserved change in pH from the stomach to the duodenum is the basis for creating pHresponsive polymers such as the commercially successful class polymers termed Eudrogit ,atrade name for copolymers based on methacrylic acid and ethyl methacrylate.Eudrogit polymers are most commonly utilized as aenteric coatings to protect sensitive payloads from the caustic environment of the stomach. [49] High molecular weight poly(acryloyl 6-aminocaproic acid; M w % 400 kDa; > 3) can be combined with linear poly-(methacrylic acid-co-ethyl acrylate) to create hydrated elastomers ( Figure 6).…”
Section: Stimuli-responsive Materialsmentioning
confidence: 99%